Reduced bone resorption and increased bone mineral density in women with restless legs syndrome. (29th March 2016) - Cikrikcioglu, Mehmet Ali; Sekin, Yahya; Halac, Gulistan; Kilic, Elif; Kesgin, Siddika; Aydin, Senay; Ozaras, Nihal; Akan, Onur; Celik, Kenan; Hamdard, Jamshid; Zorlu, Mehmet; Karatoprak, Cumali; et al.
Abstract : Objective: To investigate bone resorption and formation markers as well as bone mineral density in women with restless legs syndrome (RLS). Methods: This was a prospective cross-sectional case-control study involving drug-naive women with RLS and age- and body mass index (BMI)–matched female controls. Routine blood analyses, markers of bone formation, procollagen 1 n-terminal peptide, bone resorption, c-telopeptide of type 1 collagen (CTX), sclerostin, and bone mineral density (BMD) were compared between the 2 groups. Pregnant or breastfeeding women and individuals with comorbidities other than iron deficiency, type 2 diabetes mellitus, or hypertension were excluded. Results: A significant increase in lumbar BMD was found among 78 women with RLS as compared to 78 age- and BMI-matched controls ( p = 0.001). The proportion of patients with osteopenia as defined by a lumbar T score was significantly lower among patients with RLS ( p = 0.040). CTX and sclerostin were significantly lower in patients with RLS ( p = 0.006 and p = 0.011, respectively), as were the levels of 25-hydroxy vitamin D3, calcemia, and free T3 ( p = 0.017, p = 0.017, and p = 0.002, respectively). Conclusions: Despite lower 25-hydroxy vitamin D3, patients with RLS had lower bone resorption markers, higher lumbar BMD, and lower frequency of lumbar osteopenia. As patients with RLS make movements night and day to decrease the severity of their symptoms, they unconsciously perform exercise, which may potentially explain the better bone profile among patients with RLS than in controls.